Novel carbon-based material for perovskite solar cells back-contact - Cristina O. Teixeira (2019)
Perovskite solar cells are one of the most promising photovoltaic technology, presenting the fastest power conversion efficiency (PCE) growth from 3.8 % to 24.2 % in just 10 years. However, there are still challenges hindering its commercialization such as the expensive back-contact made of gold. Carbon-based materials, mainly carbon pastes made of carbon black and graphite, have already proven to be good candidates as back-contacts because of their features such as low cost, high conductivity, and high stability. In this work, the replacement of gold back-contact by a carbon paper with a microporous layer coated with a PEDOT:PSS dispersion is reported. To the best of the author's knowledge, this material has never been reported for perovskite solar cells. A PCE of 9.22 % was obtained, representing 62 % of the PCE obtained for the same cell but with a gold back-contact.